2016
DOI: 10.1016/j.pupt.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the cough reflex by aclidinium and tiotropium in awake and anesthetized rabbits

Abstract: a b s t r a c tLong-acting muscarinic receptor antagonists (LAMAs) have been reported to attenuate cough in preclinical and clinical studies. The present study was performed on rabbits to compare aclidinium and tiotropium efficacy in the downregulation of the cough reflex. This reflex was evoked by citric acid inhalation in unanesthetized animals and by both citric acid inhalation and mechanical stimulation of the tracheobronchial tree in anesthetized animals 90 min following the inhalation of each drug (nebul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 67 publications
(81 reference statements)
0
14
0
Order By: Relevance
“…For example, there is evidence that muscarinic antagonists reduce experimental cough,40 and that tiotropium and ipratropium act on TRPV1 to reduce the cough response in preclinical models 41. In addition, a 2016 preclinical study in rabbits showed that, further to their anticholinergic activity and any action on TRPV1 receptors, aclidinium and tiotropium may also have antitussive actions involving mechanoreceptors and acid-sensing ion channels 42. These studies provide preclinical evidence of LAMA antitussive activity; however, it is not yet clear how this may translate into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there is evidence that muscarinic antagonists reduce experimental cough,40 and that tiotropium and ipratropium act on TRPV1 to reduce the cough response in preclinical models 41. In addition, a 2016 preclinical study in rabbits showed that, further to their anticholinergic activity and any action on TRPV1 receptors, aclidinium and tiotropium may also have antitussive actions involving mechanoreceptors and acid-sensing ion channels 42. These studies provide preclinical evidence of LAMA antitussive activity; however, it is not yet clear how this may translate into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, investigations on the basic neural mechanisms subserving the cough reflex performed on healthy preparations can provide useful hints for the development of antitussive or protussive strategies (see e.g. Cinelli et al, 2016;Mutolo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Birrell and colleagues [121] showed that tiotropium, but not glycopyrronium, was able to modulate the cough reflex through the transient-potential vanilloid receptor type-1 (TRPV1) with mechanisms not related to its anticholinergic activity, but rather interacting with another binding site on the channel or by acting indirectly as a modulator of the TRPV1 channel [121]. Further insight was given by Mutolo and coworkers that suggested that the down-regulation of cough promoted by tiotropium implied also the involvement of acid-sensing ion channels and mechanoreceptors [122]. …”
Section: Introductionmentioning
confidence: 99%